Experimental and Numerical Investigation of Concrete-Filled Double-Skin Steel Tubular Column for Steel Beam Joints. (5th August 2018) - Zhang, Dongfang; Zhao, Junhai; Zhang, Yufen
Abstract : This paper presents a new type of joint for connecting steel beams with a concrete-filled double-skin steel tubular (CFDST) column. Four half-scale specimens of the joint with different specifications were constructed and tested under a constant axially compressive force with vertical low-reversal loads applied to the beam ends to examine their failure modes and hysteretic behaviors. The beam hinging mechanism of the joint was observed in the radian area of the horizontal end plates. The proposed connection was found to exhibit good energy dissipation capabilities with its limit rotation in the failure state reaching 0.05 rad, thus satisfying the FEMA-350 ductility requirement of ≥0.03 rad for seismic resistance. A finite element analysis (FEA) model of the joint was also established and validated by comparing its predictions with experimental results. The FEA model was used to investigate the effects of different parameters such as the stiffened height of the web anchorage plate, axial load level, steel and concrete strengths, steel ratio on the moment-rotation relationship, and initial stiffness of the connection. This paper presents some important design considerations of the connection, as well as aspects requiring further study.